Advances on the formation and detection of hollow heart in vegetable crops - Jiaxi Li; Jincui Jia; Zhiwei Qin; Xingwang Liu; Ming Xin (Vegetable Research)
Hollow heart is a commodity quality defect that manifests as a lack of substance in the heart region of some organs, and it is a common occurrence in vegetable crop production. This phenomenon has attracted the attention of researchers from an early stage. However, no complete system for the occurrance has been formed. In this review, the influence of environmental conditions, cultivation patterns, and hormones on the formation of hollow hearts were first analyzed. Then the recent findings of gene mapping and molecular mechanisms were discussed. Additionally, the detection of hollow heart in vegetable crops was summarized from two aspects: acoustics and optics. Finally, perspectives and suggestions were put forward for further research and interest. This review may provides a basis for further research and valuable insight for hollow heart resistance breeding.